Proteomic profiling in liver cancer: another new page - Chan, Lo-Kong; Ng, Irene Oi-Lin (Translational Gastroenterology and Hepatology, 2019)
Hepatocellular carcinoma (HCC) is one of the top lethal malignancies worldwide. HCC development is usually asymptomatic and diagnosed at the advanced stage of the disease, at which effective therapeutic options are much limited (1). Multi-kinase inhibitors Sorafenib and Lenvatinib are the two first-line drugs approved by the Food and Drug Administration (FDA) of USA for advanced HCC patients (2,3). However, the overall response rates and the survival benefits in patients treated with these agents are still far from perfect. More recently, the immunotherapy using the Nivolumab, the anti-PD1 antibody, has gained an accelerated approval by the FDA after a Phase II clinical trial as a second line therapy for advanced HCC patients (4). Although it is extremely encouraging that a subset of HCC patients showed complete cure after anti-PD1 treatment, however, the overall response rate is around 14.3%. Also, subgroup analysis has suggested that anti-PD1 therapy may be less effective in HCC with certain etiological background such as HBV infection, in which the host may be suffering from immune exhaustion which greatly limits the outcome of the therapy.